2014
DOI: 10.1007/s40534-014-0058-7
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on the aerodynamic characteristics of high-speed train under turbulent crosswind

Abstract: Increasing velocity combined with decreasing mass of modern high-speed trains poses a question about the influence of strong crosswinds on its aerodynamics. Strong crosswinds may affect the running stability of highspeed trains via the amplified aerodynamic forces and moments. In this study, a simulation of turbulent crosswind flows over the leading and end cars of ICE-2 high-speed train was performed at different yaw angles in static and moving ground case scenarios. Since the train aerodynamic problems are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 14 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…As the inter-car gap length affects the flow field and pressure distribution, the train models with several different lengths are established. Ten different lengths are 5,8,10,15,20,30,40,50,60, and 80 mm. Figure 16 shows four inter-car gaps with different lengths.…”
Section: The Effect Of Inter-car Gaps On the Aerodynamic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the inter-car gap length affects the flow field and pressure distribution, the train models with several different lengths are established. Ten different lengths are 5,8,10,15,20,30,40,50,60, and 80 mm. Figure 16 shows four inter-car gaps with different lengths.…”
Section: The Effect Of Inter-car Gaps On the Aerodynamic Characteristicsmentioning
confidence: 99%
“…The inter-car gap shown in Figure 1(e) was used in several numerical simulations. [18][19][20][21] It is concluded from the works of Watkins et al, 3 Wilmenson, 4 Kwon et al, 5 and Paul et al 6 that the inter-car gap has a significant effect on the aerodynamic drag of a train. A proper design of the intercar gap can be superior to the modification of the nose shape.…”
Section: Introductionmentioning
confidence: 99%
“…The application of CAE in virtual environment is widespread in engineering and includes railway optimisation [2,[5][6][7][8]. A study on the use of CFD to determine aerodynamic forces showed that CFD simulations are very useful for prediction of real properties [9]. Despite the fact that CAE simulations have become widespread, there has been relatively little research on brake discs in rail vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the work on trains going down the tracks have been done on high speed trains (HST), for example, bullet trains or maglev trains. Some of this computational analysis has been done without rotating wheels (Asress and Svorcan 2014). Some simulations describing the shape of the slipstream use detached eddy simulation or large eddy simulation (Baker 2014;Flynn et al 2014).…”
Section: Motivation and Challengesmentioning
confidence: 99%
“…Another issue with how trains have been studied is most of the CFD simulations are done on highly defeatured models, i.e., the bogies have been simplified to a rectangle with cylindrical wheels (Asress and Svorcan 2014;Flynn et al 2014;Östh and Krajnović 2014).…”
Section: Motivation and Challengesmentioning
confidence: 99%